Evaluation of Mashhad city parks from the conformity of child-friendly city standards - Behravesh, Hoda; Alizadeh, Katayoon; Jafari, Hamid (Cadernos de Educação Tecnologia e Sociedade, 2021)
With the current trend of urbanization and the increasing attractiveness of cities, urban environments are becoming the main bedrock of a new generation of children. The presence of children in the city is directly related to the quality of urban space and construction. Proper urban space provides a great deal of security and presence of the child and inadequate urban space eliminates it and causes a variety of social damages and problems. Public spaces such as parks and playgrounds are an important factor in socializing children (Anguluri & Narayanan, 2017). Children as the most sensitive and vulnerable group of society, while being influenced by the environment, have significant abilities in shaping or changing the environment around them (Pamela, Sruthi & Roger, 2015). Therefore, checking and evaluation of Mashhad city parks, as the second largest metropolis of Iran from the Conformity of Child-Friendly City Standards is necessary. This is an applied research that has been done by descriptive-analytical method. The target population in this thesis is 6-12 years old children, their parents and the relevant authorities or a group of experts in Mashhad according to population and housing census of 2016, who with the help of Cochran sample size formula, 390 children and parents, and 30 experts were interviewed. The studied parks in this paper are neighborhood scaled parks of Mashhad which it is a total of 528 cases, out of which 53 parks have been studied in municipalities of Mashhad. Data were analyzed using one-way chi-square, Spearman correlation coefficient, and univariate t-test. The results showed that most districts and neighborhood parks in Mashhad do not comply with the criteria and principles of child-friendly cities and physical-functional and socio-cultural components play the most roles in the presence of children in neighboring and neighborhoods scale parks in the city of Mashhad.